2022
DOI: 10.3390/foods11142135
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Volatile Compounds and Physicochemical and Sensory Characteristics of Reverse-Seared and Conventionally Seared Beef Steaks

Abstract: This study was conducted to determine the effect of heat treatment (searing and reverse searing) on the volatile components and physicochemical and sensory characteristics of beef tenderloin. In reverse-seared steaks (RSSs), the loss rate was lower than in seared steak (SS), and several free amino acids (glutamic acid, glycine, histidine, and anserine) were increased, while a decrease in fatty acids (FAs) and volatile compounds (VCs) was observed. The VCs were identified as 24 compounds: 11 aldehydes, 5 alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Similarly, Lee et al . (2022) found that no significant difference in springiness and cohesiveness between seared and reverse‐seared steaks. Similar to the present study results, Duma‐Kocan et al .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Similarly, Lee et al . (2022) found that no significant difference in springiness and cohesiveness between seared and reverse‐seared steaks. Similar to the present study results, Duma‐Kocan et al .…”
Section: Resultsmentioning
confidence: 98%
“…This result is probably related to the change of meat surface colour as a result of non‐enzymatic browning reactions such as caramelisation and Maillard due to sealing process. Similar results have been reported in many studies dealing with the effect of sealing on colour of meat (Rodas‐González et al ., 2015; Yoo et al ., 2020; Lee et al ., 2022). Indeed, the sealing process had a significant effect ( P < 0.01) on the outer surface colour of the samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhao et al [10] examined the dynamic changes in the volatile chemicals and physicochemical properties (gel strength, whiteness, and hardness) of tilapia sausage in the fermentation process and found that the main physical indexes and typical volatile compounds were both significantly enhanced after fermentation. Lee et al [11] showed that the effect of mild heat treatment of beef tenderloin reduced the formation of meat aroma but caused a remarkable increase in appearance and texture. Compared with the determination of volatiles, the analysis of quality indicators is relatively convenient.…”
Section: Introductionmentioning
confidence: 99%